(untitled) (Journal of Economic Research & Business Administration, 2015)
In this article shows the basic concepts and terminology that used in study of the problems of development management organizational systems.The author shows new approaches to improve the entire Republican economy and ensuring the development of the regional economy. The main objective of the regional economy is the development of a strategy of regional socio-economic development.